2017
DOI: 10.4102/sajbm.v48i4.39
|View full text |Cite
|
Sign up to set email alerts
|

Personality and content preferences on social network sites in South Africa

Abstract: Worldwide, visual content, such as photos and videos, have increased dramatically on social network sites (SNS), with South Africa being no exception. The purpose of this study was to investigate the relationship between two personality traits -need for cognition and need for affect -and visual and verbal content preference on SNS in South Africa. A survey was conducted and data were obtained from 307 social network site users. The main findings showed that personality does have an influence on SNS users' pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In term of information content types, the respondents of this study indicated varied preferences, including both visual and verbal. Apart from utilising different types of content (Mwaba, et al, 2017), it is necessary for the authority to thoroughly understand each content type in term of its usage and influence (Aydin, Uray & Silahtaroglu, 2021). It should also be understood that, strategic social media practices differ, often influenced by the context (Aydin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In term of information content types, the respondents of this study indicated varied preferences, including both visual and verbal. Apart from utilising different types of content (Mwaba, et al, 2017), it is necessary for the authority to thoroughly understand each content type in term of its usage and influence (Aydin, Uray & Silahtaroglu, 2021). It should also be understood that, strategic social media practices differ, often influenced by the context (Aydin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the respondents chose video, written and infographic content indicated preferences for both visual and verbal elements. It should be noted that, types of social media content preference are also influenced by users' personality traits (Mwaba, Saini & Abratt, 2017). Different messages which aim to invoke emotion or to provide mental stimulation may require different types of social media content (Mwaba et al, 2017).…”
Section: Types Of Social Media Content Preferencementioning
confidence: 99%
See 1 more Smart Citation
“…This, however, does not imply that visual is more important than verbal. Instead, both visual and verbal elements are equally important, as social media preferences can be influenced by various considerations including personality traits (Mwaba, Saini & Abratt, 2017).…”
Section: Discussionmentioning
confidence: 99%